Assessment of knowledge, Attitude and Practice of Plagiarism Among Postgraduate and Undergraduate Medical Students - Suresh Kumar, Ummehabiba, Ayesha Ahmed, Bushra Munir, Sobia Mushtaq, Naima Sher (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Scientific misconduct is a key issue in research these days and plagiarism is common practice irrespective of its awareness and consequences. Plagiarism is a theft of others ideas and intellectual property. We aimed at assessing the level of knowledge and practices regarding plagiarism in our postgraduate and undergraduate medical students. Material and Methods: A cross sectional study was conducted at Pakistan Institute of Medical Sciences, (PIMS) a constituent health facility under SZABMU, Islamabad. A total of 100 postgraduate and undergraduate students were enrolled in a period of 6 months from October 2018 to January 2019. Primary outcome measure was knowledge of plagiarism and routine practices of research and writing of the students. Data was analyzed in SPSS software. Results: Females were slightly greater in this study, both PG and UG level students were almost equal in numbers. It was noticed that 16.0% students had no knowledge regarding plagiarism. Similarly, one third (32.0%) were continuously practicing plagiarism as they felt that their peers also do so. When demographic and educational background was analyzed according to plagiarism knowledge, there was no statistical differences observed. Conclusion: Knowledge of plagiarism is not up to mark in medical students. Despite their knowledge regarding plagiarism, still one third were found confessing to continue its practice.